From Intentions to Actions: The Influence of Social Media Tourism Promotion and Travel Motivation on Tourist’s Actual Behavior (Journal of Social Sciences Review, 2025)
The purpose of the study is to examine the role of social media in tourism promotion and travel motivation within the context of Pakistan. This study investigates the influence of social media tourism promotion and travel motivation on the actual behavior of tourists, using the Theory of Planned Behavior (TPB) as the theoretical framework. A quantitative, descriptive research design with a deductive approach was employed. The population comprised followers of five Facebook pages managed by registered tour operator companies in Pakistan, with a final sample of 375 respondents selected through multi-stage probability sampling. Data were collected using a structured, closed-ended questionnaire on a 5-point Likert scale. Reliability was confirmed through a pilot study and Cronbach’s alpha analysis, with all variables exceeding acceptable thresholds. The findings suggested that majority of respondents were male (59.7%), while females made up 40.3% of the sample. This gender distribution further shows that more male tourists participated in the study than females. The results of the study confirm that social media tourism promotion has a positive and significant impact on the actual behavior of tourists. Additionally, these findings highlight the importance of social media as a tool for influencing tourist behavior. Findings of the study also revealed that behavioral intentions of tourists (BIT) significantly impact the actual behavior of tourists (ABT). In conclusion, this study confirms that social media and travel motivation significantly influence tourists’ behavioral intentions and actual travel behavior in Pakistan. The findings validate the Theory of Planned Behavior and highlight the need for strategic, motivation-aligned social media marketing by tourism operators.
Keywords: Social Media Marketing; Tourism Promotion; Theory of Planned Behavior (TPB); Travel Motivation; Tourist Behavior; Behavioral Intention; Actual Tourist Behavior